2020
DOI: 10.1186/s12879-020-05012-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of viral RNA in diverse body fluids in an SFTS patient with encephalopathy, gastrointestinal bleeding and pneumonia: a case report and literature review

Abstract: Background: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease that commonly has a lethal course caused by the tick-borne Huaiyangshan banyang virus [former SFTS virus (SFTSV)]. The viral load in various body fluids in SFTS patients and the best infection control measure for SFTS patients have not been fully established. Case presentation: A 79-year-old man was bitten by a tick while working in the bamboo grove in Nagasaki Prefecture in the southwest part of Japan. Due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Tick bite has been recognized as the main infection route, and Haemaphysalis longicornis has been identified as the predominant tick vector (Hu et al, 2020;Luo et al, 2015). It is suggested that the toll and potential threat of SFTS have been underappreciated, given the wide distribution and dispersal of the predominant tick vector (Miao et al, 2020;Rainey et al, 2018), and another transmission potential via contact with patient's blood and/or human body fluid (Akagi et al, 2020;Koga et al, 2019;Tang et al, 2013). Despite the clear public health significance, approved vaccines or specific therapeutics against SFTS are still unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…Tick bite has been recognized as the main infection route, and Haemaphysalis longicornis has been identified as the predominant tick vector (Hu et al, 2020;Luo et al, 2015). It is suggested that the toll and potential threat of SFTS have been underappreciated, given the wide distribution and dispersal of the predominant tick vector (Miao et al, 2020;Rainey et al, 2018), and another transmission potential via contact with patient's blood and/or human body fluid (Akagi et al, 2020;Koga et al, 2019;Tang et al, 2013). Despite the clear public health significance, approved vaccines or specific therapeutics against SFTS are still unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…The SFTSV viral titer was not correlated significantly with GGO abnormalities in our study; however, a quantitative RT-PCR was performed partially (72.7%) in two hospitals, and serial SFTSV follow-up measurement was performed in only 40.9% of all patients with SFTS; therefore, it was difficult to make a conclusion regarding this connection. Viral dissemination in the pulmonary alveoli was confirmed using bronchoalveolar lavage in one of our patients who presented with GGO in the lung [11], suggesting that the GGO pattern may be generated by viral dissemination and accelerated inflammation in the lung. Pleural effusion, pericardial effusion, and mediastinal lymph node enlargement in the present study (22.7%, 18.1%, and 13.6%, respectively) were similar to those in a previous study (38%, 24%, and 14%, respectively) [12].…”
Section: Discussionmentioning
confidence: 51%
“…SFTS involves multiple organs, including the liver, muscles, central nervous system, kidney, genital organs, and lungs [9][10][11]. It was reported that ∼9.6% to 28.7% of patients with SFTS experience respiratory symptoms, including cough, sputum, and dyspnea, with radiographic abnormalities being present in 29 to 45% of patients with SFTS [12].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms and epidemiological information are useful for the preliminary diagnosis of some phenuivirid diseases. However, confirmation of phenuivirid diseases should be based on symptoms, epidemiological information, and correct detection of the nucleic acids, proteins, and/or antibodies specific to relevant phenuiviruses [28,[151][152][153].…”
Section: Control Of Pathogenic Phenuivirusesmentioning
confidence: 99%